Main factors that influence colonization by yeasts of the genus of Candida in eye prostheses manufactured in acrylic resin (Research, Society and Development, 2021)
This research was an integrative review, with the objective of demonstrate the main factors that influence colonization by Candida yeasts in ocular prosthesis manufactured of acrylic resin and a microbiological composition of conjunctival secretion present in anophthalmic cavities. Published studies were retrieved through a bibliographic survey using a search strategy based on the terms: Candida; Virulence Factors; Eye Infections, Fungal; Eye, Artificial. with Inclusion criteria: articles published in Portuguese, English and Spanish; articles indexed in the databases: Latin American and Caribbean Literature in Health Sciences (LILACS), National Library Of Medicine Online (MEDLINE), Scopus and Scientific Electronic Library Online (SciELO); articles published from 2001 to 2020. And, as exclusion criteria: studies without information on sampling and analysis performed; bibliographic review studies and studies with duplicates in the databases. Among the factors that influence the colonization of ocular prostheses by Candida yeasts, the following stand out: Quality of the finishing and polishing of the prostheses; degree of surface porosity and roughness; quality of the acrylic resin used in the manufacture and degree of conversion of the polymers; frequency of cleaning of the prosthesis and conjunctival mucosa; lacrimal secretion from the anophthalmic cavity; and virulence factors of colonizing yeasts. Thus, we emphasize that the control of the microbial load of the anophthalmic cavity, through the correct use of the confection technique and good hygiene practice, is essential for rehabilitation through the use of ocular prostheses to play its role successfully.